A review of student attendance system using near-field communication (NFC) technology - Mohd Nasir, Mohd Ameer Hakim; Asmuni, Muhammad Hazimuddin; Salleh, Norsaremah; Sanjay, Misra (2015)
The rapid growth of system development is no longer subtle and continuously improving today’s system. In education sector, the student attendance system is able to be applied by Near-Field Communication (NFC) technology. NFC can be referred to as a device that can detect information and/or command from a tag by bringing them together in a close proximity or even by touching together. Traditionally, the manual attendance system would require a lecturer to pass around an attendance sheet for students to sign beside their names and another method would require the lecturer to call out the students’ names one by one and register their attendance. The attendance system based on NFC is meant to improve the manual attendance system and therefore the aim of this paper is to review the existing research on this topic.